Estudo da propagação de contaminante em aterros sanitários via GITT - Albuquerque, Flávio Alves de (2018)
Nowadays, the concern with protecting the environment and in particular with water resources is becoming more frequent. Thus, contamination of soil and groundwater from the diffusion and convection processes of the concentration of contaminants accumulating over time in landfills is an extremely important factor. The present work aims to study the propagation of the concentration of contaminants present in the soil, from the continuous and uniform pollutant leakage in an urban solid waste storage cell (RSU) in a sanitary landfill. The generalized integrated transform (GITT) technique is used to solve the problem of transport of the species in the landfill through the concentration field. The analyzes focus on obtaining parameters for use in the prevention of contamination of soil and groundwater under a sanitary landfill. A hybrid, analytical-numerical solution is presented for the mass transport equation in a saturated porous medium. GITT is used to solve these equations, in a transient regime, allowing the mathematical manipulation of the equations and their boundary conditions, even if they are nonlinear, to produce systems of ordinary differential equations for transformed potentials. The model proposed in this paper is that of Ogata (1970) and Bear (1972). A computational code was developed to obtain the concentration field from practical parameters and that help in the implantation of new sanitary landfills with a greater degree of protection.